Analisis Beban Kerja pada Unit HRD di PT. Gapura Angkasa Cabang Denpasar - Suta, I Gusti Lanang; Meliani, Syarifah Hany Putri; Sumetri, Ni Wayan; Widhari, Cokorda Istri Sri (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2022)
The role of HRD in service companies is very important, starting from being responsible for recruiting qualified HR according to the criteria then optimizing HR planning and how to use existing HR as a supporter of company growth. However, HRD employees are often overwhelmed in carrying out their duties due to personal reasons or too many workloads because they are not balanced with the appropriate number of HR. As a solution, the author wants to do research on Workload Analysis for the HRD unit at PT. Gapura Angkasa Denpasar branch aims to determine the workload of the HRD unit and determine the optimal number of employees using the Full Time Equivalent method with the hope that the research results will be taken into consideration and input for the company in an effort to optimize performance in the HRD unit. Starting from collecting the required data through a questionnaire, then processing and calculating the existing workload to measure whether each employee has been optimal, underloaded or overloaded in his workload.